Fatal Systemic Morbillivirus Infection in Bottlenose Dolphin, Canary Islands, Spain - Sierra, Eva; Zucca, Daniele; Arbelo, Manuel; García-Álvarez, Natalia; Andrada, Marisa; Déniz, Soraya; Fernández, Antonio
A systemic morbillivirus infection was diagnosed postmortem in a juvenile bottlenose dolphin stranded in the eastern North Atlantic Ocean in 2005. Sequence analysis of a conserved fragment of the morbillivirus phosphoprotein gene indicated that the virus is closely related to dolphin morbillivirus recently reported in striped dolphins in the Mediterranean Sea.